2006
DOI: 10.1200/jco.2006.06.8353
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Randomized Trial of Adjuvant Fluorouracil and Folinic Acid Compared With Surgery Alone After Resection of Colorectal Liver Metastases: FFCD ACHBTH AURC 9002 Trial

Abstract: Despite a suboptimal regimen, which was the standard at the beginning of the study, adjuvant intravenous systemic chemotherapy provided a significant disease-free survival benefit for patients with resected liver metastases from colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
323
2
15

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 509 publications
(348 citation statements)
references
References 29 publications
8
323
2
15
Order By: Relevance
“…Presently, there is no standard guideline for CLM patients after liver resection. There are a few randomised clinical trials published that evaluate the survival effects of HAI of FUdR and/or intravenous systemic chemotherapy after hepatic resection (Lygidakis et al, 1995;Asahara et al, 1998;Lorenz et al, 1998;Lorenz and Muller, 2000;Tono et al, 2000;Kemeny et al, 2002;Kemeny and Gonen, 2005;Portier et al, 2006). Most of these studies, however, have limited statistical power due to small sample sizes (less than 100 subjects) or slow accrual.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Presently, there is no standard guideline for CLM patients after liver resection. There are a few randomised clinical trials published that evaluate the survival effects of HAI of FUdR and/or intravenous systemic chemotherapy after hepatic resection (Lygidakis et al, 1995;Asahara et al, 1998;Lorenz et al, 1998;Lorenz and Muller, 2000;Tono et al, 2000;Kemeny et al, 2002;Kemeny and Gonen, 2005;Portier et al, 2006). Most of these studies, however, have limited statistical power due to small sample sizes (less than 100 subjects) or slow accrual.…”
Section: Discussionmentioning
confidence: 99%
“…An overall survival benefit was observed in two of these studies (Lygidakis et al, 1995;Asahara et al, 1998). The trial by Portier et al (2006) evaluated the survival benefits of systemic intravenous adjuvant chemotherapy and resection alone. Intravenous systemic chemotherapy following hepatectomy improved disease-free survival significantly (HR 0.66, 95% CI: 0.46 -0.96).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitry E et al reported that a pooled analysis of two randomized trials demonstrated a benefit to adjuvant 5-FU based chemotherapy in both DFS and OS (Mitry et al, 2008). The report by Portier et al represents the first publication of arandomized phase III trial comparing systemic chemotherapy after surgery to surgery alone and patients receiving postoperative systemic FU plus LV exhibited significantly better survival than those receiving surgery alone (24.4 months vs 17.6 months, respectively) (Portier et al, 2006) but, the difference did not reach a statistical significance. In two studies including 1100 and 763 patients with resected hepatic metastases of CRC, no significant benefit of adjuvant therapy after metastasectomy could be detected (Fong et al, 1999;Kato et al, 2003).…”
Section: Figure 3 Overall Survival Curve For 22 Patients Who Underwementioning
confidence: 99%
“…The overall mortality rate is 40% higher if there is a delay Ն2 months before adjuvant chemotherapy is started [59]. In one study, after resection of CRC liver metastases, adjuvant 5-FU-LV resulted in a greater 4-year DFS rate, 42% versus 32% (p ϭ .28), than with surgery alone, but did not affect the OS outcome [60]. A systematic review and meta-analysis of four studies of perioperative chemotherapy around the time of liver resection found no OS benefit (HR, 0.74; 95% confidence interval [CI], 0.53-1.04) but did find a recurrence-free survival benefit of 25% (HR, 0.75; 95% CI, 0.62-0.91) [61].…”
Section: The Role Of Adjuvant Chemotherapy After Liver Resectionmentioning
confidence: 99%